Evaluasi Kualitas Layanan Situs Web KKN Universitas Merdeka Pasuruan menggunakan Metode WebQual 4.0 dan Importance Performance Analysis (IPA) - Goesti Sofi Indah Sari; Ismiarta Aknuranda; Satrio Hadi Wijoyo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The Unmer Pasuruan KKN website is managed by the PD-MTI Unmer Pasuruan and is used for the KKN registration process as well as the media for channeling KKN information for semester 7 students. While using the site, students complain about the upload process that took so long, information that is not updated. In addition, this website has never been evaluated. From the problems that exist, the researcher assesses the need for an evaluation to measure the quality of service for the KKN website using the WebQual 4.0 method and Importance Performance Analysis (IPA) to determine the value of site attributes. This study used 22 questionnaires that adopted from WebQual 4.0. The results of the questionnaire will be analyzed using the IPA method which includes analysis of the level of conformity, gap level analysis and quadrant analysis by involving and not involving attribute number 17 namely "I feel safe to make transactions through this site", so that each calculation will produce two analyzes and discussions. The results of the suitability analysis obtained percentages of 94.92% and 94.69%, the results of the gap analysis were -0.258 and -0.269. The results of the IPA quadrant show 3 attributes in quadran I (Priorities for Improvement), 9 attributes in quadrant II (keep up the good work), 7 attributes in quadrant III (lowest priority) and 3 attributes in quadrant IV (possible overkill).